2022
DOI: 10.3390/su14116898
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering Barriers for Industrial Symbiosis: Assessing Prospects for Eco-Industrialization through Small and Medium-Sized Enterprises in Developing Regions

Abstract: Industrialization is indispensable for socio-economic development but poses far-reaching implications for resources and the environment. Consequently, industrial symbiosis-based collaborations are gaining recognition as a viable strategy to manage resource consumption for mitigating environmental distress. However, these types of synergistic collaborations are more prevalent in developed regions and are linked to larger-sized industries. Admittedly, such collaborative partnerships are less focused in developin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Other papers examine specific barriers which may be found in the case of emerging and frontier markets and some of their findings may be applicable in our case. Those barriers include, among others, financial barriers to promoting, lack of awareness of industrial symbiosis projects, deficiency of regulatory frameworks and lack of infrastructure [27,28]. Hence, looking into the data already collected, through a PESTLE questionnaire in the margins of the SWAN project, in the light of the recent findings on generic and specific barriers to industrial symbiosis and the ways of removing them [25] seems a very interesting and promising research area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other papers examine specific barriers which may be found in the case of emerging and frontier markets and some of their findings may be applicable in our case. Those barriers include, among others, financial barriers to promoting, lack of awareness of industrial symbiosis projects, deficiency of regulatory frameworks and lack of infrastructure [27,28]. Hence, looking into the data already collected, through a PESTLE questionnaire in the margins of the SWAN project, in the light of the recent findings on generic and specific barriers to industrial symbiosis and the ways of removing them [25] seems a very interesting and promising research area.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few years, this development has slowed down in Europe due to several, mostly financial, barriers (e.g., new infrastructure and physical space required, economic crisis and strict financial budget implemented for the majority of companies) [25]. Recent research, however, has identified a number of other generic IS barriers (i.e., governmental, technological, organizational) [26] but also country-specific barriers (i.e., low awareness, lack of infrastructure, absence of regulatory framework) [27,28] which may be found mainly in emerging and frontier economies and can be applicable in the case of the Balkan countries. Thus, there is currently the need for national or regional policy frameworks that will facilitate the implementation of IS, resulting in economic benefits for all stakeholders involved and improvement in the environmental performance of the system.…”
Section: Introductionmentioning
confidence: 99%
“…This percentage is less than 50%, which means agreement with the answers of the study sample. Table ( 5) contains the mean, standard deviation, and coefficient of variation for the environment dimension Where paragraph (4) ranked first, which is represented by "the company works to employ its human capabilities and exploit them positively" with an arithmetic mean of (3.78), which is greater than the general arithmetic mean of (3.45) and a standard deviation of (0.971). This is logical because most companies work to employ their human potential and exploit it positively for its survival and achieving its goals.…”
Section: Statistical Testsmentioning
confidence: 99%
“…Therefore, a company's strategy needs to be developed and modified accordingly to keep firms competitive in the long run. Hence, firms that can deliver real superior value to the customer experience via an innovative corporate strategy built on a long-term viable, sustainable basis will endure and be sustained for a long time [4,5]. Likewise, the importance of strategic planning has led to the success of thousands of large, small and medium companies and it caused an excellent competitive advantage between companies and business organizations [6].…”
Section: Introductionmentioning
confidence: 99%
“…A strong correlation was established between worker's quality and organizational success. Finally, Akhtar, et al, (2022) undertook a research on critical problems restricting SMEs in Nigeria and assessed factors influencing the level of firm success. Therefore, small enterprises were deemed to be source of job and contribute fully to gross domestic product.…”
Section: Review Of Empirical Studiesmentioning
confidence: 99%